2014
DOI: 10.1016/j.ejvs.2013.10.023
|View full text |Cite
|
Sign up to set email alerts
|

Response to ‘Re. Computed Tomography Imaging Features and Classification of Isolated Dissection of the Superior Mesenteric Artery’

Abstract: Isolated superior mesenteric artery dissection (SMAD) is a pleiomorphic disease. A systematic approach requires adequate classification. The purpose of classification is to organize patients into groups, which should be clinically informative in order to assist medical decision making. Four classification systems, which were all devised based on the imaging appearance of the SMAD, have been proposed over recent years; 1e4 however, no consensus has emerged regarding which classification system should be used. S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2017
2017
2017
2017

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 4 publications
0
1
0
Order By: Relevance
“…However, it does not consider features of the true and false lumen such as shape, whether the false lumen is thrombosed, and the stenosis of the true lumen. Therefore, Luan and Li 12) suggested that their classification scheme can well describe SISMAD when combined with Yun's classification scheme. 8) For example, when a dissection is limited to the curved part of the SMA with a visible false lumen but without a visible re-entry site, it can be described as a type B-IIa, and when the dissection extends to the distal trunk of the SMA with thrombosed false lumen and occluded true lumen, it can be described as a type C-III.…”
Section: Classifications Of Sismadmentioning
confidence: 99%
“…However, it does not consider features of the true and false lumen such as shape, whether the false lumen is thrombosed, and the stenosis of the true lumen. Therefore, Luan and Li 12) suggested that their classification scheme can well describe SISMAD when combined with Yun's classification scheme. 8) For example, when a dissection is limited to the curved part of the SMA with a visible false lumen but without a visible re-entry site, it can be described as a type B-IIa, and when the dissection extends to the distal trunk of the SMA with thrombosed false lumen and occluded true lumen, it can be described as a type C-III.…”
Section: Classifications Of Sismadmentioning
confidence: 99%